(untitled) (Transport systems and technologies, 2023)
The paper examines operations that take place at the sea container terminal in the context of a unified system of information exchange between participants in intermodal cargo transportation. The study aims to formalize the cargo handling process at the sea container terminal through the temporal logic apparatus, which allows for the distribution of the processes necessary for the cargo lots forwarding formalities at the seaport terminal, according to causal relationships in time. The urgency of the work is explained by the rapid development of containerization and the growing demand for transportation in intermodal transport units from the side of cargo owners. The feasibility of implementing "single window" systems for intermodal transportation is confirmed by the complexity of such transportation systems: the presence of several types of transportation, the requirement of a high degree of integration of transportation participants, and strict time constraints. The practical significance of the presented formalization provides an idea of the cargo handling algorithm, contributes to the qualitative formulation of the task of designing software solutions for information exchange at container terminals that shorten the cargo handling process by simplifying the document flow.